Effective Protocol for Rapid and Mass Micropropagation of Cymbidium Aloifolium (L.) Sw. Protocorms using Different Carbohydrate and Plant Growth Regulator - Noor Rohmah, Khoirista; Taratima, Worasitikulya (Food Agricultural Sciences and Technology, 2021)
Efficient in vitro propagation of Cymbidium aloifolium protocorm-like-bodies (PLBs) using carbohydrate sources and hormones as a medium supplement was established. Twelve-week-old protocorms were used as explants. Experiment 1; protocorms were propagated on solidified New Dogashima (ND) medium supplemented with various concentrations of glucose and sucrose (0, 20, 25, 30, 35 and 40 g/l) as carbohydrate sources. Experiment 2; protocorms were cultured on the same medium added 2,4-dichlorophenoxyacetic acid (2,4-D; 0, 0.5, 1 and 1,5 mg/l) combination with kinetin (0, 1 and 2 mg/l) as plant growth regulators. Survival, response, shoot number and length, root number and length, leaf number, and fresh and dry weight were measured after 12 weeks of culture. Results revealed that sucrose as the appropriate carbohydrate source for promoting shoot and leaf development while glucose was better for stimulating weight and root development. Optimal concentration of sucrose was 20-35 g/l with highest leaf number obtained at 20 g/l, shoot number at 25 g/l and shoot length at 35 g/l. The highest fresh weight, dry weight, root number and length were recorded at 35 g/l glucose treatment. Supplementation of hormone 2,4-D as auxin, and kinetin as a cytokinin produced highest growth of protocorm at 0.5 mg/l 2,4-D and 2 mg/l kinetin treatment. Different supplements and concentrations had diverse affected on root, shoot and leaf growth. These results provided valuable knowledge for future orchid conservation studies.